ANALYSIS THE ENVIRONMENTAL SUPPORT CAPACITY BASED ECOSYSTEM SERVICES TO BASIC DIRECTIONS FOR ADJUSTING THE SPACE PATTERN IN WACO REGENCY - Ahmad Rifqi Makkasau; Daud Malamassam; Anwar Umar (Universitas Andi Djemma Palopo, 2022)
Wajo Regency ecosystem has an abundance of natural and ecological resources with great potential. However, the rapid pace of development activities followed by rapid land conversion has put the sustainability of the supporting ecosystems under pressure. Therefore, it is necessary to map the carrying capacity of the environment based on ecosystem services in Wajo Regency in order to identify the fit between environmental carrying capacity and development in Wajo Regency. Research is at Wajo Regency, through the identification of land cover. ecosystem service-based land capability based analysis is conducted using an Analysis Hierarchy Process to determine the value of ecosystem services from four classes of environmental services, namely water supply, food supply, natural disaster prevention and runoff, and flood management. Instructions for completing spatial patterns in Wajo Regency are performed by analyzing the overlap of the ecosystem service-based bearing capacity map with the Wajo Regency spatial pattern map to obtain a class of spatial pattern alignment. The orientation class is based on the carrying capacity of the land capability based based on ecosystem services to optimize land cover in Wajo Regency. Results of this study show that the land capability based of the four examined ecosystem services in Wajo Regency is dominated by high and low classes. The results of the evaluation of the RTRW by Wajo Regency show that an area of 42,048.97 ha corresponds to the carrying capacity based on ecosystem services. An area of 199,454.11 hectares of land is less oriented, but most of it is retained based on the direction of the spatial pattern. In terms of environmental sustainability based on ecosystem services, the most important land accesses are in the designated settlement areas, other protected areas and local protected areas.